2016
DOI: 10.1007/s10865-016-9712-3
|View full text |Cite|
|
Sign up to set email alerts
|

The interrelations between spiritual well-being, pain interference and depressive symptoms in patients with multiple sclerosis

Abstract: Depressive symptoms are common in individuals with multiple sclerosis (MS), and are frequently exacerbated by pain; however, spiritual well-being may allow persons with MS to more effectively cope with pain-related deficits in physical and role functioning. We explored the associations between spiritual well-being, pain interference and depressive symptoms, assessing each as a potential mediator, in eighty-one patients being treated for MS, who completed self-report measures: Functional Assessment of Chronic I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 58 publications
4
32
1
Order By: Relevance
“…However, few of the authors of identified studies reported the duration of pain of their study participants. We therefore modified the inclusion criteria to include studies that explicitly said that they included participants with "chronic pain" or who had a primary medical condition often associated with chronic pain (Bartlett et al 2003;Basinski et al 2013;Büssing and Koenig 2008;Büssing et al 2009;Cooper-Effa et al 2001;Dezutter et al 2009Dezutter et al , 2010Harris et al 2017;Harrison et al 2005;Keefe et al 2001;McParland and Knussen 2010;Meier 1982;Nsamenang et al 2016;Offenbaecher et al 2017;Rzeszutek et al 2017). Also, the aims we initially proposed in the PROSPERO protocol for this systematic review included examining whether religion is associated with measures of pain and function and the extent to which pain-related beliefs, pain-coping responses, and catastrophizing in adults with chronic pain are different or similar in people with different religious affiliations.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…However, few of the authors of identified studies reported the duration of pain of their study participants. We therefore modified the inclusion criteria to include studies that explicitly said that they included participants with "chronic pain" or who had a primary medical condition often associated with chronic pain (Bartlett et al 2003;Basinski et al 2013;Büssing and Koenig 2008;Büssing et al 2009;Cooper-Effa et al 2001;Dezutter et al 2009Dezutter et al , 2010Harris et al 2017;Harrison et al 2005;Keefe et al 2001;McParland and Knussen 2010;Meier 1982;Nsamenang et al 2016;Offenbaecher et al 2017;Rzeszutek et al 2017). Also, the aims we initially proposed in the PROSPERO protocol for this systematic review included examining whether religion is associated with measures of pain and function and the extent to which pain-related beliefs, pain-coping responses, and catastrophizing in adults with chronic pain are different or similar in people with different religious affiliations.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Thus, 20 studies were included in the final analysis of the systematic review. (Ammondson 2009;Bartlett et al 2003;Cooper-Effa et al 2001;Dunn 2005;Harris et al 2017;Harrison et al 2005;Keefe et al 2001;Lavin and Park 2011;Meier 1982;Nsamenang et al 2016;Rippentrop et al 2005;Ruzicka et al 2007). All but one study (n = 19 [95%]) were cross-sectional observational studies, while one was a descriptive and exploratory mixed-method study (Ammondson 2009).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations